2021
DOI: 10.1002/exp.20210063
|View full text |Cite
|
Sign up to set email alerts
|

Multisite PCET with photocharged carbon nitride in dark

Abstract: A combination of photochemistry and proton coupled electron transfer (PCET) is a primary strategy employed by biochemical systems and synthetic chemistry to enable uphill reactions under mild conditions. Degenerate nanometer‐sized n‐type semiconductor nanoparticles (SCNPs) with the Fermi level above the bottom of the conduction band are strongly reducing and act more like metals than semiconductors. Application of the degenerate SCNPs is limited to few examples. Herein, we load microporous potassium poly(hepta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 68 publications
(98 reference statements)
0
17
0
3
Order By: Relevance
“…Due to plenty of electrons available in photocharged semiconductors at nearly the same potential, at least one example—reductive dimerization of enones—unambiguously point that reactivity of semiconductor particles under continuous light illumination (classical photocatalysis) [ 151 ] and semiconductors photocharged with e − /H + (ref. [36]) is different. Studying photocharged SCP(e − /H + ) as PCET reagents may establish a whole new field of preparative organic chemistry.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Due to plenty of electrons available in photocharged semiconductors at nearly the same potential, at least one example—reductive dimerization of enones—unambiguously point that reactivity of semiconductor particles under continuous light illumination (classical photocatalysis) [ 151 ] and semiconductors photocharged with e − /H + (ref. [36]) is different. Studying photocharged SCP(e − /H + ) as PCET reagents may establish a whole new field of preparative organic chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…[ 151 ] Addition of a ketyl radical to the starting enone 1a followed by HAT/PCET and elimination of H 2 O yields substituted hexadienone 2a . [ 36 ] Kurpil and Savateev found that under continuous illumination using triethanolamine as electron donor, selectivity is shifted to cyclopentanol 3a as the major product. [ 151 ] PCET mechanism for ketyl radical formation was concluded taking into account CB potential of K‐PHI (−0.75 V vs SCE), [ 152 ] which is not sufficiently negative to reduce enone 1a to its radical anion via electron transfer ( E 1/2 = −1.4 V vs SCE).…”
Section: Application Of Photocharged Materials For Reduction Of Organ...mentioning
confidence: 99%
See 3 more Smart Citations